The Earliest Kant in the Face of Metaphysics: a Historical Approach to the Origins of an Intellectual Attitude. —II. Intellectual Environments— - Mendoza Gurrola, Paulo Sergio (Con-Textos Kantianos. International Journal of Philosophy, 2023)
This paper continues the effort of contributing, from the Kantforschung perspective and using methodological principles of the intellectual history, to the knowledge of the immediate and general contexts in which flow the different metaphysical doctrines that Kant could know during the years of his university formation, doctrines that could influence his first attitudes in the face of metaphysics. First, it reconstructs his immediate intellectual environment making an approach to the professors that dictated metaphysics courses when Kant was student at the Albertina; then, it deals with the situation of the main metaphysics doctrines in Prussia during eighteen-century first half, particularly to face to development of modern natural science; finally, in contrasting characteristics of both immediate and general intellectual environments, it suggests an account on how young Kant’s profile could be shaped as an anti-Wolffian independent eclectic.
Keywords: pre-Critical Kant; metaphysics; neo-scholastic Aristotelianism; pietistic eclecticism; Wolffianism and anti-Wolffianism